2008
DOI: 10.1111/j.1600-0854.2008.00720.x
|View full text |Cite
|
Sign up to set email alerts
|

A New Role for Nuclear Transport Factor 2 and Ran: Nuclear Import of CapG

Abstract: The small GTPase Ran plays a central role in nucleocytoplasmic transport. Nuclear transport of Ran itself depends on nuclear transport factor 2 (NTF2). Here, we report that NTF2 and Ran control nuclear import of the filamentous actin capping protein CapG. In digitonin‐permeabilized cells, neither GTPγS nor the GTP hydrolysis‐deficient Ran mutant RanQ69L affect transit of CapG to the nucleus in the presence of cytosol. Obstruction of nucleoporins prevents nuclear transport of CapG, and we show that CapG binds t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
37
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 54 publications
4
37
0
Order By: Relevance
“…Purification of Myc-CapG-V5-His 6 has been previously described [10]. Human His 6 -RanQ69L and His 6 -Ran wild-type were expressed and purified as described [19].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Purification of Myc-CapG-V5-His 6 has been previously described [10]. Human His 6 -RanQ69L and His 6 -Ran wild-type were expressed and purified as described [19].…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, we reported that CapG interacts directly with Ran GTPase [10]. Since Ran is predicted to localize in the nucleolus by a proteome study (http://www.lamondlab.com/NOPdb/) and has been reported to accumulate in the nucleolus in in vitro experiments [23], we also tested Ran in our experiments (Fig.…”
Section: Capg Is Actively Transported To the Nucleolusmentioning
confidence: 99%
See 3 more Smart Citations